جهود المستشرقين ضد الإسلام والمسلمين: إنكار الوحي أنموذجا: The efforts of orientalists against Islam and Muslims: denying revelation as a model DOI:10.5281/zenodo.13738621 (Khairulummah, 2024)
This study aims at the position of orientalists and negative efforts with the approach of tracking opinions, and  the suspicions of orientalists and their efforts about the revelation of the Holy Quran and Sunnah of the Prophet. It shows the methods taken by orientalists to suspicious and questioning their source. Some orientalists have taken the similarity between the texts Holy Qur'an and the texts contained in other heavenly books means in the Torah and the Bible as evidence that the Holy Qur'an was taken by the Prophet (Allah peace be upon him) from these heavenly books, and not on the one hand Allah certainly.The Muslims scholars have responded to these suspicions, and explained the serious errors in them that are due to the fact that those in charge of these translations do not speak the Arabic language, although they are students and readers of it, but they have not been able to identify the secrets of the Arabic language, which is the language of the Holy Qur'an. This study also presents the responses of Islamic scholars and conclusion in the end of research.
Keywords: Efforts , orientalists, Islam, Muslims, denying revelation